Post Disaster Illumination for Underground Mines - Vamsi Krishna S; Nitai Pal; Pradip Kumar Sadhu (Institute of Advanced Engineering and Science, 2015)
Lighting systems provide mine workers improved visibility and contribute to improved safety, productivity, and morale. Lighting is critical to miners, since they depend heavily on visual cues to spot fall of ground, pinning & striking and slipping & tripping hazards. Most conventional systems of lighting are used in mines are extracting a lots of power and deal with major maintenance problems. Apart from the conventional grid-power lighting systems, additional emergency lighting system using green energy is mandatory in case of grid-power failure or in disaster situation of the underground mines. The luminous efficacy increases with switching frequency while providing eye comfort to user. Even though CFL has low power consumption for solar photovoltaic (SPV) power system, but CFL’s electrical requirements are not easily met by hard-switched inverters due to their higher switching losses at higher frequencies and preheat and ignition voltage of CFL results lower efficiency. This paper demands well suited high frequency inverter and a series interrupting type charge controller for illumination at remote areas. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7069